2010
DOI: 10.3109/01421590903394587
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the effects of an international health professions faculty development fellowship: the FAIMER Institute

Abstract: While there are many examples of evaluations of faculty development programs in resource rich countries, evaluation of transnational programs for faculty from developing countries is limited. We describe evaluation of the effects of the FAIMER Institute, an international health professions education fellowship that incorporates not only education content, but also leadership and management topics and, in addition, strives to develop a sustained community of educators. Data were obtained via retrospective pre/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 49 publications
4
50
0
Order By: Relevance
“…Confidence and competence, is supported by others (Burdick et al 2010) whose participants reported application of new leadership-related concepts to the workplace, following their faculty development program. This finding is also supported by outcomes of other research on faculty development (Peters et al 2002;Muller and Irby 2006;Srinivasan et al 2007).…”
Section: Figure 2 Domains Of Leadership Developmentmentioning
confidence: 99%
“…Confidence and competence, is supported by others (Burdick et al 2010) whose participants reported application of new leadership-related concepts to the workplace, following their faculty development program. This finding is also supported by outcomes of other research on faculty development (Peters et al 2002;Muller and Irby 2006;Srinivasan et al 2007).…”
Section: Figure 2 Domains Of Leadership Developmentmentioning
confidence: 99%
“…The FAIMER Institute (Burdick, Diserens et al 2010 There are 3-and a 2-week residential sessions one year apart in Philadelphia and two 11-month online discussions conducted via a list serve. Both formal and informal meetings during the residential sessions foster cross-cultural understanding by encouraging fellows to share information about their ethnicity, religion, political influences, food, dress, and language.…”
Section: Educational Setting and Participantsmentioning
confidence: 99%
“…Discourse theories provide heuristics, which can be used to explore relationships between power, privilege, and identity. participating in communal activity, and continuously creating a shared identity by engaging in and contributing to the practices of their communities (Norcini J, Burdick W,Morahan P, 2005) forms a community of cross-cultural practice (Burdick, Diserens et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…This report responds to this research question through retrospective qualitative analysis of the reported experiences of health professions faculty members from 18 countries who implemented education innovation projects at their home institutions. The challenges encountered and skills needed for project success are viewed through the lens of the Foundation for the Advancement of International Medical Education and Research (FAIMER) Institute, a two-year faculty development Fellowship with on-site sessions located in Philadelphia, USA (Norcini et al 2005;Burdick et al 2006;Burdick et al 2010).…”
Section: Practice Pointsmentioning
confidence: 99%
“…Each Fellow develops his/her project rationale, identifies desired outcomes for the particular project, and designs and implements project evaluation in conjunction with the project itself. Previous analysis of skills gained from the Fellowship as well as focus and impact of projects has been reported (Burdick et al 2010;Burdick et al 2011 (Cousins & Whitmore 1998;Fetterman et al 2010). Transcripts of interviews with and written reports from 54 mid-career health professions faculty members (30 men and 24 women) from 18 countries who participated in the two-year FAIMER Institute program between 2001 and 2006 formed the basis of the data in this study.…”
Section: Practice Pointsmentioning
confidence: 99%